The familial language debate: understanding a complex issue through the lenses of theology and anthropology - Norris, Johnathan (Missiology, 2017)
This article will explore the controversy surrounding translating the familial terms Son of God and Father in Muslim contexts. Specifically, this analysis will use the lenses of biblical and systematic theology as well as cultural and linguistic anthropology to understand the debate holistically, instead of viewing the debate through a single discipline. Each discipline will be explored separately and sympathetically. The insights gained from these disciplines will be brought into a concluding synthesis, which I hope sheds more light on the familial terms debate.